A Universal Design for Success: A Mixed-Methods Case Study of a First-Year BScN Course (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2021)
No single universal learner type exists, however historically, pedagogical practices in higher education have focused on meeting the learning needs of an average or typical student. The purpose of this study was to describe the manner and extent in which a course, designed using Universal Design for Learning (UDL) principles, provided an inclusive learning environment to a diverse population of first-year baccalaureate nursing students. Co-instructors redesigned a large in-person and place-based course using theoretical and structural principles of UDL to remove potential learning barriers and promote authentic inclusion of all students. A convergent mixed methods descriptive case study design was used to gather qualitative and quantitative data. A purposive convenience sample was drawn from a class of 223 full and part time nursing students. Qualitative data were collected through an end of semester focus group interview (n = 12) and research team meetings. Quantitative data collection involved using the Inclusive Teaching Strategies Inventory-Students survey questionnaire (Gawronski, et al., 2016) at course completion (n = 32), and document review of final grades (n = 206). The use of UDL principles in the design and teaching supported the needs and abilities of learners with a variety of learning preferences and experience. Students experienced a more inclusive environment with fewer barriers to learning. Large in-person and place-based post-secondary courses designed using the key tenets of UDL successfully support inclusivity of the needs of learners with diverse backgrounds, abilities, and preferences, by proactively reducing barriers in the learning environment.